First‐In‐Human Safety, Tolerability, and Pharmacokinetics of PPI‐1011, a Synthetic Plasmalogen Precursor - Tara Smith; Kaeli J. Knudsen; Shawn A. Ritchie (Clinical and Translational Science)
ABSTRACT PPI‐1011 is a synthetic plasmalogen precursor designed to augment plasmalogen levels in patients with Rhizomelic chondrodysplasia punctata (RCDP), an ultra‐rare genetic disorder caused by a plasmalogen deficiency that results in significant physical and mental delays. We report here a Phase I, randomized, double‐blind, placebo‐controlled study that evaluated the safety, tolerability, and pharmacokinetics (PK) of single (10–100 mg/kg) and multiple (75 and 100 mg/kg/day) ascending doses of PPI‐1011 in healthy adults. All treatment‐emergent adverse events (TEAEs) were mild, monitorable, and resolved without intervention, suggesting no significant safety concerns. The most common TEAEs were gastrointestinal in both the placebo and PPI‐1011 groups, suggesting they were likely related to the oil‐based nature of the formulation. PK analysis confirmed that both single (25, 50, 75 and 100 mg/kg) and multiple‐dose (75 and 100 mg/kg, once daily) administration of PPI‐1011 significantly increased serum levels of the target plasmalogen (PlsEtn 16:0/22:6). With a once‐daily regimen, PPI‐1011 administration resulted in a sustained increase of PlsEtn 16:0/22:6 serum concentrations in healthy participants over a duration of 14 days and beyond.